Optimizing video feedback for snatch technical error correction in young weightlifters: Comparing the effectiveness of different video playback speeds - Souissi, M. A.; Trabelsi, O.; Tounsi, O.; Hawani, A.; Fekih, S.; Souissi, H.; Gharbi, A.; Amor, A.; Scharenberg, S.; Souissi, N. (International Journal of Sports Science & Coaching, 2024)
Researchers are actively recommending optimal modes of usage for techno-pedagogical tools to ensure that athletes reap the benefits of technology in their training. In this study, we investigated the most effective video feedback viewing speed among normal-speed (NS), half-speed (HS), and quarter-speed (QS), for technical error correction in young weightlifters during the snatch movement. A total of 37 weightlifters (25 boys and 12 girls), aged 11-12 years, were randomly divided into three groups, namely the normal-speed (control group), the half-speed, and the quarter-speed group. Participants completed a pretest (T0), a seven-week snatch learning unit, and a posttest (T1), as well as a retention test one week later (T2). Video-mediated technical analysis of the snatch movement was conducted using the Kinovea motion analysis software. The main results showed that weightlifters who viewed their feedback videos at a quarter of the normal speed (QS) achieved significantly greater improvements in the displacement of the bar in the first pull Dx2 (T1 vs. T0: 27.41 ± 26.10%, Hedges` g = 0.87, p < 0.05; T2 vs. T0: 24.34 ± 27.11%, Hedges` g = 1.07, p < 0.05) and the vertical displacement VTR (T1 vs. T0: 22.89 ± 14.16%, Hedges` g = 1.16, p < 0.05) compared to those who viewed the videos at NS or HS. These findings suggest that slowing down video feedback playback to a quarter of the normal speed can be an effective strategy for enhancing technical error correction in young weightlifters.